(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The integration of Information and Communication Technology (ICT) and multimedia within History teaching and learning is an outcome of the curriculum of the National Education Department of South Africa. History lessons for the classroom situation can become more active and learner centred, slowing the widening gap between South Africa and the developed world with respect to ICT integration and the use of multimedia resources in History teaching and learning at schools. The purpose of this article is to show teachers where to locate sources and resource materials that can be used in History lessons, inform teachers on some of the History-related features of each website, and expose teachers to the use of new teaching strategies aided by the Internet. High-tech TLSM possibilities can promote greater integration of ICT and multimedia into History lessons to improve a broader understanding of content and enhance quality teaching.